Midodrine treatment for chronic fatigue syndrome. Issue 942 (13th April 2004) - Naschitz, J; Dreyfuss, D; Yeshurun, D; Rosner, I
Abstract : The long term results of midodrine treatment in a patient having debilitating chronic fatigue syndrome (CFS) are reported. Midodrine treatment, directed at the autonomic nervous system, resulted in correction of the dysautonomia followed by improvement of fatigue. This finding is consistent with the hypothesis that dysautonomia plays a major part in the pathophysiology of CFS and that therapies directed at the autonomic nervous system may be effective in the treatment of CFS.